ADVANCING GREEN ELECTRICITY THROUGH SOLAR PANEL-BASED STREET LIGHTING WITH LIGHT SENSOR INTEGRATION IN RANGKAPAN JAYA VILLAGE, DEPOK - Ni Putu Devira Ayu Martini; Silvia Anggraeni; Ayu Mika Sherila; Vina Sari Yosephine; Sanggi Bayu Ardika; Anis Fitri Nur Masruriyah (Institut Teknologi dan Bisnis Swadharma, 2026)
The growing demand for sustainable energy solutions has highlighted the importance of renewable energy technologies, particularly in urban and semi-urban communities. In Rangkapan Jaya Village, Depok, the lack of adequate street lighting and limited awareness of green energy solutions have created both environmental and safety challenges. This project contributes a replicable model for integrating solar-powered street lighting (PJUTS) into underserved communities using a participatory approach. It also provides a practical framework for community-based training in renewable energy technology, promoting both infrastructure development and environmental education. The activity began with a socialization session explaining the principles and benefits of renewable energy and solar panels. This was followed by hands-on technical training on the installation of PJUTS systems, involving local residents directly in assembling and deploying the equipment in targeted areas. Participants demonstrated increased understanding of solar panel operation and installation. Several solar-powered streetlights were successfully installed, improving lighting in previously unlit areas. Community feedback indicated heightened interest in renewable energy solutions and greater confidence in maintaining the system independently. The project shows that a community-based, educational approach is effective in promoting green technology at the local level. It addressed both practical infrastructure needs and capacity-building, offering a scalable solution for other regions seeking sustainable energy implementation.Peningkatan kebutuhan terhadap solusi energi berkelanjutan mendorong pemanfaatan teknologi energi terbarukan, khususnya pada lingkungan masyarakat perkotaan dan semi-perkotaan. Di Kelurahan Rangkapan Jaya, Depok, keterbatasan fasilitas penerangan jalan serta rendahnya pemahaman masyarakat mengenai konsep energi hijau menjadi tantangan yang berdampak terhadap aspek lingkungan dan keamanan. Kegiatan pengabdian kepada masyarakat ini bertujuan untuk menerapkan sistem penerangan jalan umum tenaga surya (PJUTS) berbasis sensor cahaya sekaligus meningkatkan pengetahuan dan keterampilan masyarakat dalam pemanfaatan teknologi energi terbarukan melalui pendekatan partisipatif. Metode pelaksanaan kegiatan meliputi sosialisasi mengenai prinsip kerja dan manfaat energi terbarukan, pelatihan teknis instalasi sistem PJUTS, praktik perakitan perangkat, serta pemasangan sistem penerangan pada lokasi yang telah ditentukan. Kegiatan ini melibatkan masyarakat secara langsung dalam proses instalasi dan pemeliharaan sistem. Hasil kegiatan menunjukkan bahwa peserta mengalami peningkatan pemahaman terkait prinsip kerja panel surya, sensor cahaya, dan sistem penyimpanan energi. Selain itu, beberapa unit penerangan berbasis energi surya berhasil dipasang dan mampu meningkatkan pencahayaan pada area yang sebelumnya minim penerangan. Kegiatan ini menunjukkan bahwa pendekatan edukatif berbasis partisipasi masyarakat efektif dalam mendukung penerapan teknologi hijau di tingkat lokal. Implementasi PJUTS tidak hanya memberikan solusi terhadap kebutuhan infrastruktur penerangan, tetapi juga meningkatkan kapasitas masyarakat dalam mendukung pemanfaatan energi berkelanjutan